Anticancer Characteristics of Fomitopsis pinicola Extract in a Xenograft Mouse Model—a Preliminary Study. (18th May 2020) - Kao, Chi H. J.; Greenwood, David R.; Jamieson, Stephen M. F.; Coe, Margaret E.; Murray, Pamela M.; Ferguson, Lynnette R.; Bishop, Karen S.
Abstract: Introduction: Medicinal mushrooms have been used for the treatment of diseases and general promotion of health for many centuries. Recent pharmacological research into medicinal mushrooms has identified various therapeutic properties, with applications in modern medicine. Aim: To evaluate the anti-cancer activities of Fomitopsis pinicola ( F. pinicola ) alcoholic extract in an in vivo setting. Methods: The anti-tumour effect of the F. pinicola extract was tested in a xenograft immune-compromised Rag-1 mouse model. This was followed by RT-PCR and metabolomics analyses. Results: There were no observable differences in tumor growth between treated and non-treated groups. The bioactive components were not detected in the mouse plasma or the tumor site. Conclusions: The extract was poorly absorbed; this is likely due to the timing of treatment, dosage levels and modifications made to the extract where the alcohol-based solvent was replaced with water. This, in combination with fractionation studies which identified most anti-cancer compounds to be hydrophobic, largely explained the lack of anti-cancer activities in vivo.